Multi-element microalloyed high-strength corrosion-resistant magnesium alloy bar and preparation method thereof

By adding low-potential elements La, Ca and Y to the magnesium alloy, combined with the extrusion and rotary forging deformation process, the problem of insufficient corrosion resistance and mechanical properties of magnesium alloy is solved, and its corrosion resistance in the marine environment is significantly improved and mechanical properties realize the potential of low-cost large-scale applications.

CN119243001AActive Publication Date: 2025-01-03SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411793553.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-03
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The application of magnesium alloys in aerospace and other fields is limited by their poor corrosion resistance and mechanical properties, especially in marine environments, which are prone to microgalvanic corrosion, and the addition of a large number of rare earth elements increases the cost and limits its large number of Scale application.

Method used

Using multivariate microalloyed high-strength corrosion-resistant magnesium alloy rods, the Al2Ca, Al11La3 and Al2Y intermetallic compound particles are formed by adding low potential La, Ca and Y elements to the magnesium alloy, and the grains are refined to reduce the volume of Mg17Al12 phase. The mechanical properties are significantly improved through extrusion and rotary forging deformation process.

Benefits of technology

It significantly improves the mechanical properties and corrosion resistance of magnesium alloys, reduces the corrosion rate, forms a dense oxide film, enhances the corrosion resistance of magnesium alloys, and gives it a wide application potential in the fields of aerospace and marine ships.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243001A_ABST
    Figure CN119243001A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium alloys, and particularly discloses a multi-element microalloying high-strength corrosion-resistant magnesium alloy bar and a preparation method thereof. The multi-element microalloying high-strength corrosion-resistant magnesium alloy bar comprises the following chemical components in percentage by mass: 6-7% of Al, 0.1-0.15% of La, 0.1-0.15% of Ca, 0.1-0.15% of Y and the balance of Mg and inevitable impurities, the magnesium alloy bar is of a multi-phase structure, a magnesium matrix is of a close-packed hexagonal crystal structure, and the multi-element microalloying high-strength corrosion-resistant magnesium alloy bar is obtained through extrusion and bar rotary swaging deformation process treatment. The multi-element microalloyed high-strength corrosion-resistant magnesium alloy bar prepared by the invention has the advantages of high strength and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of magnesium alloys, and more specifically, to a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod and a preparation method thereof. Background Art

[0002] As the lightest metal structural material, magnesium alloy has broad application prospects in aerospace, marine ships, automobiles, 3C electronic products, and biomedical fields due to its high specific strength, excellent damping and shock absorption performance, good electromagnetic shielding performance, and biocompatibility. With the rapid development of science and technology and the implementation of the dual carbon policy, lightweighting has become a development trend in these fields, and magnesium alloy has a unique advantage in lightweighting, with a density of only 2 / 3 of aluminum and 1 / 4 of steel. However, magnesium and its alloys are chemically active and have the lowest standard electrode potential (-2.37V / SHE) among structural metals. Usually, the alloying elements added to magnesium alloys have a more positive electrode potential than magnesium, so the second phase formed in magnesium alloys is usually a cathode phase, which leads to microgalvanic corrosion of magnesium alloys and deteriorates their corrosion resistance. In addition, the greater the potential difference between the alloying elements and the magnesium matrix, the more severe the microgalvanic corrosion will be. In addition, in terms of kinetics, the PBR (Pilling-Bedworth ratio) of the MgO oxide film formed by natural oxidation on the magnesium surface is 0.81, which is less than 1, that is, the oxide film formed cannot densely cover the surface of the magnesium matrix. Therefore, in the marine environment, corrosive chloride ions can easily destroy the magnesium oxide film and induce local corrosion. Ultrapure magnesium without other alloying elements usually has excellent corrosion resistance (0.25mm / year), but due to the poor mechanical properties of pure magnesium, it cannot be directly used for structural parts. The addition of a large amount of rare earth alloying elements can significantly improve the mechanical properties of magnesium alloys through precipitation strengthening, such as Mg-Gd-Y-Zr alloy, whose strength can reach 500MPa, but the precipitation of a large amount of high-potential second phase will significantly deteriorate its corrosion performance. In addition, the addition of a large amount of expensive rare earth elements makes the alloy unable to be used on a large scale. The traditional commercial AZ91 magnesium alloy usually has poor corrosion resistance due to the addition of high potential Zn elements (-0.76 / SHE) and Mn elements (-1.18V / SHE). In addition, its low mechanical properties also limit its application in complex and harsh environments. Therefore, the development of high-strength and corrosion-resistant magnesium alloys is the key to promoting the application of magnesium alloys in aerospace and other fields. Summary of the invention

[0003] In order to further improve the strength and corrosion resistance of magnesium alloys, the present application provides a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod and a preparation method thereof.

[0004] In the first aspect, the present application provides a multi-element microalloyed high-strength and corrosion-resistant magnesium alloy bar, which adopts the following technical solution: A multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod comprises the following chemical components based on mass percentage: 6-7% Al, 0.1-0.15% La, 0.1-0.15% Ca, 0.1-0.15% Y, and the balance is Mg and inevitable impurities. The magnesium alloy rod has a multiphase structure, wherein the magnesium matrix has a close-packed hexagonal crystal structure.

[0005] Preferably, the unavoidable impurity elements include Fe, Ni, and Cu, and the total impurity content is less than 0.02%.

[0006] In a second aspect, the present application provides a method for preparing the above-mentioned multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod, comprising the following steps: (1) Pure magnesium ingots, pure aluminum ingots, Mg-30La master alloy, Mg-30Ca master alloy, and Mg-30Y master alloy were weighed according to the chemical composition of the magnesium alloy, and preheated to remove moisture before smelting; (2) melting under CO2 and SF6 protective gas, adding pure magnesium ingot, pure aluminum ingot, Mg-30La master alloy, Mg-30Ca master alloy and Mg-30Y master alloy into a graphite crucible at different temperatures to obtain a magnesium alloy melt; (3) Under the protection of CO2 and SF6, the magnesium alloy melt is sequentially refined, stirred, and allowed to stand for heat preservation to fully purify the melt and allow impurities to sink to the bottom of the crucible, thereby obtaining a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6, the oxide slag on the surface of the purified magnesium alloy melt is removed, and then the magnesium alloy melt is cast into a preheated metal mold to obtain a magnesium alloy ingot; (5) The magnesium alloy ingot is first subjected to a solution treatment, and then extruded into a rod. The rod is subjected to a multi-pass rotary forging treatment on a rotary forging machine to obtain a multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod.

[0007] Preferably, the volume ratio of CO2 to SF6 is 1:(9-10).

[0008] Preferably, the specific operation of step (2) is: under CO2 and SF6 protective gas, add pure magnesium ingot at 550-650°C, heat to 680-700°C to melt magnesium, heat to 710-730°C, add pure aluminum ingot, then increase to 740-760°C, add Mg-La master alloy, Mg-Ca master alloy, Mg-Y master alloy in sequence, and then keep warm until all alloys are melted to obtain a magnesium alloy melt.

[0009] Preferably, in step (3), the refining temperature is 740-760°C, and the refining agent is added while stirring during refining, and stirring is continued for 10-20 minutes to fully react with impurities in the melt; the standing temperature and time are: first standing at 740-750°C for 30-40 minutes, and then cooling to 700-710°C and standing for 20-30 minutes.

[0010] Preferably, in step (3), the composition of the refining agent is 45-49wt% KCl, 24-28wt% CaCl2, 10-14wt% BaCl2, 6-8wt% CaF2, and 7-9wt% YCl3; the amount of the refining agent added is 1-2% of the total mass of the magnesium alloy.

[0011] Preferably, in step (4), the casting temperature is 690-700°C, and the metal mold preheating temperature is 180-220°C.

[0012] Preferably, in step (5), the solution treatment temperature is 400-420°C and the time is 20-28 hours; the extrusion molding process is: extrusion temperature 350-400°C, extrusion speed 0.5-1m / min, extrusion ratio (24-26):1, extrusion into rods; the rotary forging process is: at room temperature, the extruded rods are subjected to rotary forging treatments of different deformation passes in sequence.

[0013] Preferably, in step (5), the diameter of the rod before rotary forging is 15-20 mm.

[0014] In summary, this application has the following beneficial effects: 1. This application uses low-cost and widely used Mg-Al alloy as the basis, and performs microalloying by adding low-potential La (-2.379 / SHE), Ca (-2.76 / SHE), and Y (-2.37 / SHE). The addition of a small amount of La, Ca, and Y elements can avoid the formation of a large amount of second phases; the addition of Ca, La, and Y can preferentially combine with the Al element in the melt to form Al2Ca, Al 11 La3 and Al2Y intermetallic compound particles act as heterogeneous nucleation particles and refine the grains; the preferential combination of Ca, La, and Y elements with Al can reduce the coarse network Mg 17 Al 12The volume fraction of the phase is reduced, thereby improving the mechanical properties of the alloy and inhibiting microgalvanic corrosion; due to the addition of low potential difference La, Ca and Y elements, the generated second phase has a low potential difference with the magnesium matrix, thereby significantly inhibiting the microgalvanic corrosion between the second phase and the magnesium matrix; the PBRs of the oxides Al2O3, La2O3 and Y2O3 formed by Al, La and Y elements are 1.28, 1.11 and 1.13, respectively, which can effectively fill the loose structure of the MgO oxide film and enhance the density of the oxide film; in addition, the addition of rare earth La and Y elements can purify the melt during the smelting process and reduce the influence of impurity Fe elements on the corrosion resistance.

[0015] 2. The present invention can significantly refine the grain and the second phase structure of magnesium alloy by the method of extrusion plus rotary forging secondary deformation, so that the coarse mesh Mg 17 Al 12 The phase transformation is into fine particles, which significantly reduces the microgalvanic corrosion of the coarse network second phase on the magnesium matrix and avoids the appearance of large cathode phase and small anode phase; the large amount of dislocation density and grain refinement introduced during the rotary forging process can significantly improve the mechanical strength of the alloy; the load applied during the rotary forging process is evenly distributed along the radial direction, which can effectively avoid the material from breaking during the processing; the large amount of dislocations and other defects introduced during the rotary forging process can promote the nano-spherical Mg 17 Al 12 The uniform precipitation of the phase makes the second phase in the magnesium matrix more uniform, which can avoid the concentration of local corrosion; compared with the coarse Mg 17 Al 12 In comparison, the nano-spherical Mg 17 Al 12 The phase can significantly reduce the micro-galvanic corrosion effect with the magnesium matrix. 17 Al 12 Compared with the severe local pitting corrosion caused by the phase, the alloy of the present application exhibits uniform corrosion behavior, which is more conducive to the formation of uniform corrosion product film and the improvement of corrosion resistance.

[0016] 3. This application is based on low-cost Mg-Al alloys, and has the potential for low-cost large-scale production by adding a small amount of low-cost La, Y, and Ca elements for microalloying. In addition, the deformation process of this application is conventional extrusion plus bar forging, which can produce large-sized magnesium alloy bars. The alloy bars of this application can be used in the fields of aerospace and marine ships. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 : SEM image of the multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod prepared in Example 1 of the present application.

[0018] Figure 2 : Corrosion cross-section diagram of the multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod prepared in Example 1 of the present application after being immersed in a 3.5wt% NaCl solution for 7 days.

[0019] Figure 3 : The corrosion cross-sectional morphology of the Mg-7Al alloy rod prepared in Comparative Example 1 of the present application after being immersed in a 3.5wt% NaCl solution for 7 days. DETAILED DESCRIPTION

[0020] The present application is further described in detail below in conjunction with embodiments.

[0021] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0022] Mg-Al alloys are the most widely used magnesium alloys in commercial applications. The maximum solid solubility of Al in Mg is about 12.7%, and the solid solubility at room temperature is only about 2%. Since the Al surface has a dense Al2O3 oxide film, proper solid solution of Al can improve the chemical stability of the Mg matrix, promote the formation of a surface passivation film, and improve corrosion resistance. However, excessive addition of Al will lead to a large amount of network Mg 17 Al 12 The formation of phases leads to the decrease of mechanical properties and deformation ability of the alloy, and accelerates the micro-galvanic corrosion of the magnesium matrix. However, the addition of a small amount of Al has limited improvement on corrosion resistance, so the Al content in the alloy of the present application is in the range of 6-7wt%. The addition of a small amount of La, Y and Ca elements can significantly refine the coarse Mg 17 Al 12 The addition of La, Y, and Al elements can synergistically promote the compactness and passivation performance of the oxide film.

[0023] Example Example 1 A multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod, comprising the following chemical components, based on mass percentage: 7% Al, 0.1% La, 0.1% Ca, 0.1% Y, and the remainder Mg and inevitable impurities, wherein the inevitable impurity elements include Fe, Ni, and Cu, and the total impurity content is 0.015%; the magnesium alloy rod is a multiphase structure, wherein the magnesium matrix is ​​a close-packed hexagonal crystal structure.

[0024] The multi-element microalloyed high-strength corrosion-resistant magnesium alloy rod is prepared by the following steps: (1) Pure magnesium ingots, pure aluminum ingots, Mg-30La master alloy, Mg-30Ca master alloy, and Mg-30Y master alloy were weighed according to the chemical composition of the magnesium alloy, and preheated to remove moisture before smelting; (2) Smelting is carried out under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), adding pure magnesium ingot at 600°C, heating to 690°C to melt the magnesium, raising the temperature to 720°C, adding pure aluminum ingot, and then raising the temperature to 750°C, adding Mg-30La master alloy, Mg-30Ca master alloy, and Mg-30Y master alloy in sequence, and then keeping the temperature until all alloys are melted to obtain a magnesium alloy melt; (3) refining the magnesium alloy melt at 750° C. under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), adding a refining agent (the composition of the refining agent is 49wt% KCl, 24wt% CaCl2, 14wt% BaCl2, 6wt% CaF2, 7wt% YCl3, and the amount of the refining agent is 1.5% of the total mass of the magnesium alloy) while manually stirring, and stirring vigorously for 10 minutes, then standing at 750° C. for 35 minutes, and finally cooling to 710° C. and standing for 25 minutes for iron reduction treatment to obtain a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), the furnace temperature is lowered to 690°C, the slag on the surface of the magnesium alloy melt is scraped off, and the magnesium alloy melt is cast into a metal mold preheated at 200°C to obtain a magnesium alloy ingot; (5) The obtained magnesium alloy ingot was subjected to a solution treatment at a temperature of 400°C for 24 hours. The solution treated ingot was then extruded into a rod at 350°C with an extrusion ratio of 25:1 and an extrusion speed of 0.5 m / min. The diameter of the obtained rod was 18 mm. The obtained rod was subjected to a rotary forging treatment on a rotary forging machine at room temperature, with a deformation of 3%, 3%, 5%, 4%, 4%, 4%, and 3% in sequence. The total deformation was 26%, and a multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod was obtained.

[0025] After testing, the chemical composition of the multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod prepared in this embodiment is as follows: 7.10wt% Al, 0.12wt% La, 0.11wt% Ca, 0.11wt% Y, and unavoidable impurities include: 0.0048wt% Fe, 0.0010wt% Ni, 0.0008wt% Cu, and the balance is Mg.

[0026] The mechanical properties and corrosion properties of multi-element microalloyed high-strength corrosion-resistant magnesium alloy bars are shown in Table 1. The microstructure SEM images are shown in Figure 1 As shown. Figure 1 It can be seen that a large number of fine and dispersed spherical Mg 17 Al 12 Phase. Uniform and finely dispersed Mg 17 Al 12 phase can effectively reduce Mg 17 Al 12 The micro-galvanic corrosion effect of the cathode on the magnesium matrix can avoid the coarse network Mg in the traditional AZ91 alloy. 17 Al 12 The local pitting caused by the phase makes the alloy corrosion more uniform. In addition, the nano-scale fine dispersed Mg 17 Al 12 The second phase can significantly improve the mechanical properties of the alloy through strengthening. In addition, compared with the coarse network phase, the fine and dispersed spherical Mg 17 Al 12 The phase can effectively avoid stress concentration during deformation, making the alloy deformation more uniform and improving the mechanical properties of the alloy. Figure 2 As shown, from Figure 2 It can be seen that the alloy of the present application has a uniformly covered corrosion product film morphology after being immersed in the corrosive medium for 7 days. The thickness of the corrosion film is about 2-3μm, indicating that the substrate is uniformly corroded and the amount of corrosion is small. It can also be found that the corrosion film of the alloy is very dense and well combined with the magnesium matrix, which shows that the present application significantly improves the density and integrity of the alloy corrosion film through a variety of microalloying elements, so that the alloy still has a low corrosion rate under long-term immersion in the corrosive medium.

[0027] Example 2 A multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod, comprising the following chemical components, based on mass percentage: 7% Al, 0.12% La, 0.1% Ca, 0.1% Y, and the remainder Mg and inevitable impurities, wherein the inevitable impurity elements include Fe, Ni, and Cu, and the total impurity content is 0.018%; the magnesium alloy rod is a multiphase structure, wherein the magnesium matrix is ​​a close-packed hexagonal crystal structure.

[0028] The multi-element microalloyed high-strength corrosion-resistant magnesium alloy rod is prepared by the following steps: (1) Pure magnesium ingots, pure aluminum ingots, Mg-30La master alloy, Mg-30Ca master alloy, and Mg-30Y master alloy were weighed according to the chemical composition of the magnesium alloy, and preheated to remove moisture before smelting; (2) Smelting is carried out under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), adding pure magnesium ingot at 550°C, heating to 680°C to melt the magnesium, raising the temperature to 710°C, adding pure aluminum ingot, and then raising the temperature to 740°C, adding Mg-30La master alloy, Mg-30Ca master alloy, and Mg-30Y master alloy in sequence, and then keeping the temperature until all alloys are melted to obtain a magnesium alloy melt; (3) refining the magnesium alloy melt at 740° C. under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), adding a refining agent (the composition of the refining agent is 45wt% KCl, 28wt% CaCl2, 10wt% BaCl2, 8wt% CaF2, 9wt% YCl3, and the amount of the refining agent is 1% of the total mass of the magnesium alloy) while manually stirring, and continuously stirring vigorously for 15 minutes, then standing at 740° C. for 40 minutes, and finally cooling to 700° C. and standing for 30 minutes for iron reduction treatment to obtain a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), the furnace temperature is lowered to 695°C, the slag on the surface of the magnesium alloy melt is scraped off, and the magnesium alloy melt is cast into a metal mold preheated at 180°C to obtain a magnesium alloy ingot; (5) The obtained magnesium alloy ingot was subjected to a solution treatment at a temperature of 410°C for 28 hours. The solution treated ingot was then extruded into a rod at 380°C with an extrusion ratio of 24:1 and an extrusion speed of 0.8 m / min. The diameter of the obtained rod was 15 mm. The obtained rod was subjected to a rotary forging process at room temperature on a rotary forging machine with a deformation of 3%, 3%, 5%, and 4% in turn. The total deformation was 15%, and a multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod was obtained.

[0029] After testing, the chemical composition of the multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod prepared in this embodiment is as follows: 6.2wt% Al, 0.15wt% La, 0.13wt% Ca, 0.12wt% Y, and unavoidable impurities include: 0.0054wt% Fe, 0.0005wt% Ni, 0.0009wt% Cu, and the balance is Mg.

[0030] The mechanical properties and corrosion properties of the obtained multi-component microalloyed high-strength corrosion-resistant magnesium alloy rod are shown in Table 1.

[0031] Example 3 A multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod, comprising the following chemical components, based on mass percentage: 7% Al, 0.15% La, 0.1% Ca, 0.1% Y, and the remainder Mg and inevitable impurities, wherein the inevitable impurity elements include Fe, Ni, and Cu, and the total impurity content is less than 0.010%; the magnesium alloy rod is a multiphase structure, wherein the magnesium matrix is ​​a close-packed hexagonal crystal structure.

[0032] The multi-element microalloyed high-strength corrosion-resistant magnesium alloy rod is prepared by the following steps: (1) Pure magnesium ingots, pure aluminum ingots, Mg-30La master alloy, Mg-30Ca master alloy, and Mg-30Y master alloy were weighed according to the chemical composition of the magnesium alloy, and preheated to remove moisture before smelting; (2) Smelting is carried out under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:10), adding pure magnesium ingot at 650°C, heating to 700°C to melt the magnesium, raising the temperature to 730°C, adding pure aluminum ingot, and then raising the temperature to 760°C, adding Mg-30La master alloy, Mg-30Ca master alloy, and Mg-30Y master alloy in sequence, and then keeping the temperature until all alloys are melted to obtain a magnesium alloy melt; (3) refining the magnesium alloy melt at 760° C. in the presence of CO2 and SF6 (the volume ratio of CO2 to SF6 is 1:10) protective gas, adding a refining agent (the composition of the refining agent is 47wt% KCl, 26wt% CaCl2, 12wt% BaCl2, 7wt% CaF2, 8wt% YCl3, and the amount of the refining agent is 2% of the total mass of the magnesium alloy) while stirring manually, and stirring vigorously for 20 minutes, then standing at 745° C. for 30 minutes, and finally cooling to 705° C. and standing for 20 minutes for iron reduction treatment to obtain a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:10), the furnace temperature is lowered to 700°C, the slag on the surface of the magnesium alloy melt is scraped off, and the magnesium alloy melt is cast into a metal mold preheated at 220°C to obtain a magnesium alloy ingot; (5) The obtained magnesium alloy ingot was subjected to a solution treatment at a temperature of 420°C for 20 hours. The solution treated ingot was then extruded into a rod at 400°C with an extrusion ratio of 26:1 and an extrusion speed of 1 m / min. The diameter of the obtained rod was 20 mm. The obtained rod was subjected to a rotary forging treatment on a rotary forging machine at room temperature, with a deformation of 3%, 3%, 5%, 4%, 4%, and 3% in sequence. The total deformation was 22%, and a multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod was obtained.

[0033] After testing, the chemical composition of the multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod prepared in this embodiment is as follows: 7.20wt% Al, 0.15wt% La, 0.15wt% Ca, 0.14wt% Y, and unavoidable impurities include: 0.0042wt% Fe, 0.0004wt% Ni, 0.0005wt% Cu, and the balance is Mg.

[0034] The mechanical properties and corrosion properties of the multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rods are shown in Table 1.

[0035] Comparative Example Comparative Example 1 A Mg-7Al alloy rod, based on mass percentage, contains the following chemical composition: 7% Al, the balance is Mg and inevitable impurities, the total content of the inevitable impurity elements is 0.04%; the magnesium alloy rod has a two-phase structure, wherein the magnesium matrix is ​​a close-packed hexagonal crystal structure, and the Mg 17 Al 12 The phase has a cubic crystal structure.

[0036] The Mg-7Al alloy rod is prepared by the following steps: (1) Pure magnesium ingots and pure aluminum ingots are weighed according to the chemical composition of the magnesium alloy and preheated to remove moisture before smelting; (2) Smelting is carried out under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), adding pure magnesium ingots at 600°C, heating to 690°C to melt the magnesium, raising the temperature to 720°C, adding pure aluminum ingots, and then keeping the temperature until all the alloys are melted to obtain a magnesium alloy melt; (3) refining the magnesium alloy melt at 750° C. under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), adding a refining agent (the composition of the refining agent is 49wt% KCl, 24wt% CaCl2, 14wt% BaCl2, 6wt% CaF2, 7wt% YCl3, and the amount of the refining agent is 1.5% of the total mass of the magnesium alloy) while manually stirring, and stirring vigorously for 10 minutes, then standing at 750° C. for 35 minutes, and finally cooling to 710° C. and standing for 25 minutes for iron reduction treatment to obtain a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6 (the volume ratio of CO2 and SF6 is 1:9), the furnace temperature is lowered to 690°C, the slag on the surface of the magnesium alloy melt is scraped off, and the magnesium alloy melt is cast into a metal mold preheated at 200°C to obtain a magnesium alloy ingot; (5) The obtained magnesium alloy ingot was subjected to a solution treatment at a temperature of 400°C for 24 hours. The solution treated ingot was then extruded into a rod at 350°C with an extrusion ratio of 25:1 and an extrusion speed of 0.5 m / min. The diameter of the obtained rod was 18 mm. The obtained rod was subjected to a rotary forging treatment on a rotary forging machine at room temperature, with a deformation of 3%, 3%, 5%, 4%, 4%, 4%, and 3% in sequence, with a total deformation of 26%, to obtain a Mg-7Al alloy rod.

[0037] After testing, the chemical composition of the Mg-7Al alloy rod prepared in this embodiment is as follows: 7.20wt% Al, inevitable impurities include: 0.0080wt% Fe, 0.0010wt% Ni, 0.0010wt% Cu, and the balance is Mg.

[0038] The mechanical properties and corrosion properties of the obtained Mg-7Al alloy rod are shown in Table 1.

[0039] Its corrosion cross section is as follows Figure 3 As shown, from Figure 3 It can be seen that the corrosion resistance of traditional Mg-Al alloys is poor, and the corrosion section depth is about 200μm. It can also be found that the corrosion products have obvious cracks and the thickness is extremely uneven, indicating that serious local corrosion behavior has occurred. This is mainly due to the loose and insufficiently dense corrosion product film on the surface of traditional magnesium alloys, which can be easily destroyed by corrosive chloride ions.

[0040] Comparative Example 2 A commercial AZ80 alloy ingot was used to perform the same extrusion and swaging treatment as in Example 1. The chemical composition of the AZ80 alloy ingot was: 8.10wt% Al, 0.45wt% Zn, 0.26wt% Mn, 0.0061wt% Fe, 0.0011wt% Ni, and 0.0010wt% Cu.

[0041] (1) The AZ80 alloy ingot was subjected to a solution treatment at a temperature of 400°C for 24 hours. The solution treated AZ80 ingot was then extruded into a rod at 350°C with an extrusion ratio of 25:1 and an extrusion speed of 0.5 m / min to obtain a rod with a diameter of 18 mm.

[0042] (2) The obtained rod was subjected to rotary forging treatment on a rotary forging machine at room temperature, with deformation amounts of 3%, 3%, 5%, 4%, 4%, 4%, and 3% in sequence, and the total deformation amount was 26%, thereby obtaining an AZ80 alloy rod.

[0043] The mechanical properties and corrosion properties of the obtained AZ80 alloy rod are shown in Table 1.

[0044] Comparative Example 3 A commercial extruded AZ80 alloy was used for comparison. The AZ80 alloy ingot contained: 8.10wt% Al, 0.45wt% Zn, 0.26wt% Mn, 0.0061wt% Fe, 0.0011wt% Ni, and 0.0010wt% Cu.

[0045] The AZ80 ingot was subjected to a solution treatment at a temperature of 400°C for 24 hours, and then the solution treated AZ80 ingot was extruded into a rod at 350°C with an extrusion ratio of 25:1 and an extrusion speed of 0.5 m / min to obtain an AZ80 extruded rod.

[0046] The mechanical properties and corrosion properties of the obtained AZ80 alloy rod are shown in Table 1.

[0047] Performance testing Mechanical properties test: The gauge size of the tensile sheet used is 25×6×2mm, with three parallel specimens, and the tensile test standard complies with the national standard GB / T228.1-2021.

[0048] Corrosion performance test: The corrosion test solution is a neutral 3.5wt% NaCl solution, the test temperature is room temperature 25℃, the sample size is 20×20×5mm, and the test time is 7 days. The immersion corrosion test complies with the national standard GB10124-88. The weight loss rate is calculated by calculating the difference between the weight of the sample before the corrosion test and the weight of the sample after the corrosion test cleaning. Weight loss rate (mg / cm 2 / day) is equal to the weight difference divided by the surface area of ​​the sample divided by the number of test days, which can be converted into the average depth corrosion rate (mm / year) through the formula conversion. The volume of hydrogen gas released by magnesium corrosion is equivalent to the volume of hydrogen gas released by the simple hydrogen release test device. The hydrogen release rate (mL / cm 2 / day). The corrosion cleaning agent is a mixed aqueous solution of CrO3 and AgNO3 (wherein, CrO3 is 200g / L and AgNO3 is 10g / L). It is a general cleaning method for magnesium alloy corrosion products and complies with the national standard GB / T16545-2015.

[0049] The test results of the mechanical properties and weight loss hydrogen evolution rate of the magnesium alloy rods prepared in each embodiment and each comparative example are shown in Table 1.

[0050] Table 1 Mechanical properties and corrosion performance test results of magnesium alloys in the examples and comparative examples

[0051] As can be seen from Table 1, compared with Comparative Examples 1 to 3, the multi-component microalloyed high-strength corrosion-resistant magnesium alloy bars prepared in Examples 1 to 3 of the present application have excellent mechanical properties and corrosion resistance, with a yield strength of up to 462 MPa, a tensile strength of 445 MPa, an elongation of 2.7%-5.7%, and a weight loss rate as low as 0.087 mg / cm 2 / day, the maximum hydrogen evolution rate is 0.16mL / cm 2 / day, and the corrosion rate is as low as 0.18mm / y.

[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A multi-component microalloyed high-strength and corrosion-resistant magnesium alloy bar, characterized in that: The magnesium alloy rod comprises the following chemical components based on mass percentage: 6-7% Al, 0.1-0.15% La, 0.1-0.15% Ca, 0.1-0.15% Y, and the remainder is Mg and inevitable impurities. The magnesium alloy rod has a multiphase structure, in which the magnesium matrix has a close-packed hexagonal crystal structure.

2. The multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod according to claim 1, characterized in that: The unavoidable impurity elements include Fe, Ni, and Cu, and the total impurity content is less than 0.02%.

3. A method for preparing a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Pure magnesium ingots, pure aluminum ingots, Mg-30La master alloy, Mg-30Ca master alloy, and Mg-30Y master alloy were weighed according to the chemical composition of the magnesium alloy, and preheated to remove moisture before smelting; (2) melting under CO2 and SF6 protective gas, adding pure magnesium ingot, pure aluminum ingot, Mg-30La master alloy, Mg-30Ca master alloy and Mg-30Y master alloy into a graphite crucible at different temperatures to obtain a magnesium alloy melt; (3) Under the protection of CO2 and SF6, the magnesium alloy melt is sequentially refined, stirred, and allowed to stand for heat preservation to fully purify the melt and allow impurities to sink to the bottom of the crucible, thereby obtaining a purified magnesium alloy melt; (4) Under the protective gas of CO2 and SF6, the oxide slag on the surface of the purified magnesium alloy melt is removed, and then the magnesium alloy melt is cast into a preheated metal mold to obtain a magnesium alloy ingot; (5) The magnesium alloy ingot is first subjected to a solution treatment, and then extruded into a rod. The rod is subjected to a multi-pass rotary forging treatment on a rotary forging machine to obtain a multi-element microalloyed high-strength and corrosion-resistant magnesium alloy rod.

4. The method for preparing a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod according to claim 3, characterized in that: The volume ratio of CO2 and SF6 is 1:(9-10).

5. The method for preparing a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod according to claim 4, characterized in that: The specific operation of step (2) is as follows: under the protection of CO2 and SF6 gas, add pure magnesium ingot at 550-650°C, heat to 680-700°C to melt the magnesium, heat to 710-730°C, add pure aluminum ingot, then increase the temperature to 740-760°C, add Mg-30La master alloy, Mg-30Ca master alloy, Mg-30Y master alloy in sequence, and then keep warm until all alloys are melted to obtain a magnesium alloy melt.

6. The method for preparing a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod according to claim 5, characterized in that: In step (3), the refining temperature is 740-760°C, and the refining agent is added while stirring during refining, and stirring is continued for 10-20 minutes to fully react with impurities in the melt; the standing temperature and time are: first standing at 740-750°C for 30-40 minutes, and then cooling to 700-710°C and standing for 20-30 minutes.

7. The method for preparing a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod according to claim 6, characterized in that: In step (3), the composition of the refining agent is 45-49wt% KCl, 24-28wt% CaCl2, 10-14wt% BaCl2, 6-8wt% CaF2, and 7-9wt% YCl3; the amount of the refining agent added is 1-2% of the total mass of the magnesium alloy.

8. The method for preparing a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod according to claim 7, characterized in that: In step (4), the casting temperature is 690-700°C and the metal mold preheating temperature is 180-220°C.

9. The method for preparing a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod according to claim 8, characterized in that: In step (5), the solution treatment temperature is 400-420°C and the time is 20-28 hours; the extrusion molding process is: extrusion temperature 350-400°C, extrusion speed 0.5-1m / min, extrusion ratio (24-26):1, extrusion into rods; the rotary forging process is: at room temperature, the extruded rods are subjected to rotary forging treatments of different deformation passes in sequence.

10. The method for preparing a multi-component microalloyed high-strength and corrosion-resistant magnesium alloy rod according to claim 9, characterized in that: In step (5), the diameter of the rod before rotary forging is 15-20 mm.

Citation Information

Patent Citations

  • Ca and heavy rare earth Gd-containing die-casting heat resisting magnesium alloy and preparation thereof

    CN101353746A

  • Flame retardant magnesium alloy with excellent mechanical properties, and preparation method thereof

    CN102712969A

  • Low-cost high-strength anti-fatigue nonflammable wrought magnesium alloy and preparation method thereof

    CN105779834A

  • Creep-resistant Mg-Al wrought magnesium alloy and preparation method thereof

    CN115652158A

  • Aluminum-containing high-corrosion-resistance magnesium alloy and preparation method thereof

    CN116837261A

Cited By

  • High-corrosion-resistance magnesium alloy plate with filiform corrosion characteristic and preparation method of high-corrosion-resistance magnesium alloy plate

    CN119663081A

  • High-strength and high-corrosion-resistance magnesium alloy plate and preparation method thereof

    CN120330558A

  • Low-cost high-strength high-corrosion-resistance magnesium alloy and preparation method thereof

    CN120624905A